Building a refugee camp : the importance of planning and logistics - Abikova, Jana (London : SAGE Publications: SAGE Business Cases Originals, 2023)
The country of Rancho faces serious internal conflict, which has forced thousands of people to flee their homes. They are looking for safety in a neighbouring country, Alcoe. After crossing its borders, they reach the city of Sierra Vista and settle in various public places. International organisations and the local community urge the government to act and support incoming people. After days of inaction, displaced people have been transferred to the refugee camp. As someone with expertise in humanitarian logistics, you have been called in to consult with community, business, and government stakeholders to make various decisions that will ensure safety for both the refugees and the local residents, and ensure that health and hygiene standards are met. Once the immediate crisis settles a little, you will likely be called on to help authorities and service providers address additional operational matters in the camp.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Humanitarian assistance; Crisis management; Business logistics; Refugees -- Services for; Refugee camps